1999
DOI: 10.1038/44176
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome signalling is mediated through nucleoside diphosphate kinase 2

Abstract: Because plants are sessile, they have developed intricate strategies to adapt to changing environmental variables, including light. Their growth and development, from germination to flowering, is critically influenced by light, particularly at red (660 nm) and far-red (730 nm) wavelengths. Higher plants perceive red and far-red light by means of specific light sensors called phytochromes(A-E). However, very little is known about how light signals are transduced to elicit responses in plants. Here we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
246
1
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(257 citation statements)
references
References 26 publications
7
246
1
3
Order By: Relevance
“…More recently, a phytochrome-interacting molecule, NDPK2 (for nucleoside diphosphate kinase 2), has been reported to have a kinase activity and is involved in the response of both PhyA and PhyB. NDPK2-GFP fusion proteins are localized in both the nuclei and the cytoplasm (Choi et al, 1999). Considering the lightdependent subcellular partitioning of phytochrome and its possible interaction with those molecules in the cytoplasm or the nucleoplasm, phytochrome may have multiple sitespecific signaling mechanisms within the cell.…”
Section: Light-regulated Nuclear Import Of Phytochromesmentioning
confidence: 99%
“…More recently, a phytochrome-interacting molecule, NDPK2 (for nucleoside diphosphate kinase 2), has been reported to have a kinase activity and is involved in the response of both PhyA and PhyB. NDPK2-GFP fusion proteins are localized in both the nuclei and the cytoplasm (Choi et al, 1999). Considering the lightdependent subcellular partitioning of phytochrome and its possible interaction with those molecules in the cytoplasm or the nucleoplasm, phytochrome may have multiple sitespecific signaling mechanisms within the cell.…”
Section: Light-regulated Nuclear Import Of Phytochromesmentioning
confidence: 99%
“…Both phyA and phyB translocate to the nucleus in response to red or far-red light signals (Kircher et al, 1999;Yamaguchi et al, 1999). phyA or phyB have also been demonstrated to interact with PHYTO-CHROME INTERACTING FACTOR 3 (PIF3), PKS1, NPDK2, PIF4, ARR4, and ELF3 in vitro (Choi et al, 1999;Fankhauser et al, 1999;Ni et al, 1999;Liu et al, 2001;Sweere et al, 2001;Huq and Quail, 2002;Kim et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in human erythrocytes dimers of nm23-H1 and of glyceraldehyde-3-phosphate dehydrogenase form a heterotetrameric complex that has Ser/Thr phosphotransferase activity (Engel et al, 1998). In Arabidopsis, interaction between phytochrome B and NDPK 2 has been shown to occur (Choi et al, 1999). Also commonly found but less studied is the interaction of NDPK with heat shock proteins.…”
mentioning
confidence: 99%
“…Besides this housekeeping function, recent reports have revealed the involvement of animal NDPKs in other vital processes such as control of cell proliferation (Cipollini et al, 1997), regulation of transcription (Postel et al, 1993;Ji et al, 1995), and protein phosphotransferase (Engel et al, 1998;Wagner and Vu, 2000). In plants, phytochrome B response (Choi et al, 1999), UV-B light signaling (Zimmermann et al, 1999), and hormone responses (Nato et al, 1997;Novikova et al, 1999) are among the processes in which NDPK isoforms have been shown to be involved.…”
mentioning
confidence: 99%